EDD 703: Complex Organizations Designed for Diversity, Equity, Inclusion, and Accessibility
This course examines modern theories of complex organizations and applies them to educational institutions in diverse communities. Theories of classic management, bureaucracy, psychology of organizations, politics of internal and external organizational spaces, the culture of organizations, and organizational change processes will be examined. Students apply the theories to their own problem-of-practice to be able to design and facilitate equity-minded, transformational systemic changes.